Leveraging Instagram to enhance self-esteem: A self-affirmative intervention study and multilevel mediation analysis - KHOO, Shuna Shiann (Institutional Knowledge at Singapore Management University, 2024)
Although studies have consistently indicated that heavier use of social networking sites (SNS) perpetuates poorer self-esteem outcomes, no study has examined potential intervention methods that can yield positive effects from SNS use. We hypothesized that viewing one's Instagram profile would have self-affirmative effects on self-perception because the profile typically showcases curated instrumental positive aspects of self. Furthermore, these self-affirmative effects would indirectly improve state self-esteem via enhanced clarity of self-concept. To test our hypothesis, we designed an experimental intervention study where one group viewed their Instagram profile regularly, while another group viewed a neutral abstract art profile. Using multilevel latent variable path analyses, we found that participants who viewed their own Instagram profiles felt more positive about themselves (i.e., higher state self-esteem), and their enhanced self-concept clarity mediated the relations between self-affirmative SNS use and state self-esteem. Our findings provide preliminary evidence for the guided use of SNS to boost self-esteem.